A.S Pushkin Influence in Russian Literary Literature - Naini, Margarita Olegovna; Sudardi, Bani; Wibowo, Prasetyo Adi Wisnu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper discusses the influence of Alexander Sergeevich Pushkin in the development of Russian Classical Literature. A.S. Pushkin, a great Russian writer in the 1800s. His contribution to the development of Russian literature cannot be seen as an eye. A.S. Pushkin was not only a poet, but also the greatest Russian writer. Alexander Pushkin's work is not only favored by literary activists, but his works are able to make changes to Russian literature. The development of Russian language literature until now has never fallen away from a Pushkin. Great Russian writer who has been recognized all over the world until now.